International Monetary Fund Annual Report 2004 : Making the Global Economy Work for All. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2004)
This 2004 Annual Report highlights that during FY2004, the IMF continued to work with its member countries to foster sustained growth and financial stability-and reduce poverty in its low-income members-through its surveillance activities and policy advice; lending in support of stabilization and reform programs; and technical assistance in formulating sound policies and building robust institutions. As in previous years, a major part of the IMF's activities during the financial year were directly related to its responsibility for overseeing the international monetary system and the economic, financial, and exchange rate policies of member countries.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet